Dietary Intake of Mycotoxin Susceptible Foods by Brazilian Nursing Mothers - Tonon, Karina M.; Reiter, Mercedes G.R.; de Oliveira Dutra, Milena; Savi, Geovana D.; Scussel, Vildes M. (Current Nutrition & Food Science, 2020)
Background: The human milk has several health benefits to the mother and child, and it is the ideal form of nutrition for infants. However, some food contaminants such as mycotoxins can be transferred from the mother to the child through breast milk. Objective: To access the dietary intake of mycotoxin susceptible foods by nursing mothers. Methods: The dietary intake of mycotoxin susceptible foods was investigated by interviewing nursing mothers (n = 86), who were registered donors of the Human Milk Bank (HMB) of Blumenau (Brazil), through a food frequency questionnaire (FFQ). The mothers were contacted and those who agreed to answer the FFQ were recruited for the study group. The interview was conducted individually, face to face with each mother, by a trained researcher. The FFQ was divided into three food Groups (vegetables, animal and beverages, respectively), considered most prone to mycotoxins contamination. Socio-demographic characteristics of the mothers were also obtained. Results: The FFQ revealed a high weekly intake of foods susceptible to fungi and mycotoxin contamination. Consumption of wheat, coffee and cow’s milk was reported by 52, 44 and 51% of the mothers, respectively. The consumption of those foods occurred daily to more than 7 times per week. Conclusion: The study revealed that Brazilian nursing mothers frequently consume foods susceptible to mycotoxin contamination, especially wheat and its by-products. Brazilian health, environmental and agriculture authorities should pay permanent attention by applying monitoring programs to grains and cereals - both imported and domestically produced - as they are highly susceptible to fungi and mycotoxin contamination, which can be transferred to infants via breastfeeding, apart from harming the general population health.
Keywords: food safety